Measurement of critical current of HTSC; 4th International Conference CRYOGENICS'96, Praha, Czech Republic, 23-26 April, 1996 - Uchaykin (Uchaikin) S. V. Sergey Victorovich (1996, 1996)
В фонде НТБ ТПУ отсутствует